UJI AKTIVITAS ANTIBAKTERI EKSTRAK ETIL ASETAT DAUN TIGARON (Crataeva nurvala Buch. Ham) TERHADAP Staphylococcus aureus DENGAN METODE SUMURAN - Putri Kartika Sari; Nanda Amelia Rahmi; Fitriyanti Fitriyanti (Klinikal Sains : Jurnal Analis Kesehatan, 2024)
Staphylococcus aureus infection is characterized by tissue damage accompanied by purulent abscesses. Antibiotics are a group of drugs using to treat and prevent bacterial infections. However, long-term use causes antibiotic resistance. Efforts made to increase antibiotic resistance include using natural ingredients as alternative treatments. Tigaron is an empirical medicinal plant whose leaves are used to treat abscesses, wounds and skin diseases. This research aims to determine the types of secondary metabolite compounds and antibacterial activity against Staphylococcus aureus from ethyl acetate extract of tigaron leaves (Crataeva nurvala Buch. Ham). This research was experimental with a post test only control group design with 7 concentration variations. Extraction made by maceration using ethyl acetate, identification of secondary metabolite using phytochemical screening, antibacterial activity tested using well diffusion method. The results showed that concentration ​​of 0.31 mg/mL, 1.55 mg/mL and 7.75 mg/mL were in medium category. Concentrations of 38.75 mg/mL and 193.75 mg/mL were in strong category. Chloramphenicol as a positive control had strongest inhibition zone diameter. The conclusion are ethyl acetate extract of tigaron leaves contain alkaloid, flavonoid and steroid which inhibiting the growth of Staphylococcus aureus, so it has the potential to be a natural antibiotic using to treat infectious diseases